MEMBANGUN HUBUNGAN INTERPERSONAL POSITIF MELALUI KESEPADANAN KALIMAT TANYA DAN UNSUR NONVERBAL DI KELAS I SEKOLAH DASAR - Taufina Taufina (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Interrogative sentence is one of verbal communication forms which is commonly used in classroom interaction. This type of sentence should be synchronized with its nonverbal elements. It is believed that verbal communication that goes with its nonverbal elements would be the basis for constructing positive thinking pattern and students’ behavior, especially those in grade I of Primary School. Therefore, the teachers’ expertise in synchronizing the interrogative sentences with its nonverbal elements is absolutely necessary. Such skill would help the teacher to enhance the students’ self-confidence and enthusiasm in learning. Furthermore, it could establish positive interpersonal relationship between the teacher and the students. Hence, the teacher, as one factor in determining the success of the learning process, should concern with the synchronization between interrogative sentence and its nonverbal elements to build conducive and interactive atmosphere in the classroom